Impactos das Tecnologias da Informação e Comunicação (TIC) nas relações empregatícias: reflexos da violação ao direito à desconexão - Takano, Camila Cardoso (2021)
Through a historical conception, especially from the last decades of the 20th century, it can be seen that societies have been going through countless transformations in the digital era. These changes have reverberated in the fundamental rights of workers and in their modern employment relations. In this sense, the present dissertation aims to analyze the right to disconnection in the face of the information society. For this purpose, the research makes a critical analysis about the right to disconnection in several perspectives: regarding the new second dimension right, in relation to the new labor forms instituted in the contemporaneity, regarding the normatization of the referred institute, in the case of the violation of the disconnection, and in the field of the compensation for existential damage as a form of integral reparatory solution. In the course of this work, the approaches are analyzed in comparison with the recent jurisprudence of the E. Regional Labor Courts, as well as the C. Superior Labor Court. The methodology used was deductive, mostly, based on bibliographic review and analysis of normative instruments, supported by national jurisprudence.